Propostas para o aperfeiçoamento da cobrança do crédito tributário - Saldanha, Raquel Rayane de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
This article aims to propose effective ways to collect the tax credit, given the worrying scenario of tax foreclosures in Brazil due to their time, the resources spent to pursue them and, above all, the results achieved through them. The problem to be investigated is: how to make the collection of tax credits more efficient in Brazil? The general objective of this paper is to propose ways that, in fact, make it possible to reduce the difference between the expected revenue from tax credits due and the amounts actually received by the Public Treasury for these securities. As for the methodology chosen for this, the research has a theoretical nature, doctrinal, normative and jurisprudential analysis. It also makes use of an analysis of data released by the National Council of Justice on the subject, among other technical studies. In its final considerations, this research concluded by the viability of finding solutions for the tax authorities outside the judiciary, through a better performance of the Public Administration, in a tendency to dejudicialization in certain cases.
Artigo acadêmico
Keywords: Efetividade; Execução Fiscal; Crédito tributário; Effectiveness; Tax Enforcement; Tax Credit; CIENCIAS SOCIAIS APLICADAS::DIREITO